Teaching children about immunization in a digital age - Kumanan Wilson; Katherine Atkinson; Natasha Crowcroft (Taylor & Francis Group, 2017)
We believe that public health efforts to address issues of vaccine hesitancy should increase their focus on childhood education. An opportunity exists to create positive, accurate vaccine attitudes through fun and interactive approaches early in life. Leveraging digital technologies may provide a way to deliver these messages to children in a way that complements immune system and immunization education in school curricula. We recommend that public health officials explore and identify the most effective ways to deliver positive digital messages to children in hopes of "inoculating" the next generation against vaccine hesitancy.